Circumferential tissue compression at the lower limb during walking, and its effect on discomfort, pain and tissue oxygenation: Application to soft exoskeleton design. (July 2020) - Kermavnar, Tjaša; O'Sullivan, Kevin J.; Casey, Vincent; de Eyto, Adam; O'Sullivan, Leonard W.
Abstract: Soft exoskeletons apply compressive forces at the limbs via connection cuffs to actuate movement or stabilise joints. To avoid excessive mechanical loading, the interface with the wearer's body needs to be carefully designed. The purpose of this study was to establish the magnitude of circumferential compression at the lower limb during walking that causes discomfort/pain. It was hypothesized that the thresholds differ from those during standing. A cohort of 21 healthy participants were tested using two sizes of pneumatic cuffs, inflated at the thigh and calf in a tonic or phasic manner. The results showed lower inflation pressures triggering discomfort/pain at the thigh, with tonic compression, and wider pneumatic cuffs. The thresholds were lower during walking than standing still. Deep tissue oxygenation increased during phasic compression and decreased during tonic compression. According to the findings, circumferential compression by soft exoskeletons is preferably applied at anatomical sites with smaller volumes of soft tissue, using narrow connection cuffs and inflation pressures below 14 kPa. Highlights: The thigh and calf were subject to pneumatic cuff compressed to simulate soft exoskeleton use. Discomfort thresholds were lower during walking than standing still. Deep tissue oxygenation increased for phasic compression and decreased for tonic compression. Circumferential compression is preferably applied at anatomical sites with smaller volumes of soft tissue.